Serum Interleukin- 6, Tumor Necrosis Factor-α, D-Dimer after recombinant human brain natriuretic peptide combined with levosimendan in patients with heart failure : serum markers after heart failure treatment - Zhang, Yujing (Journal of Medical Biochemistry, 2025)
0